Проблемы создания системы глобального дистанционного зондирования Земли в ИК-диапазоне - Formozov, B. N. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
An analysis is presented of the development of technical support for Earth remote sensing tasks in the United States in light of the ABM Treaty of 1972 and the national interests of European states. It is proposed to establish, on a cooperative basis, a constellation of 3–4 geostationary stabilized platforms equipped with television instruments based on multi-matrix focal arrays sensitive in the 3 and 5 μm ranges. The feasibility of cryostatting multi-matrix focal arrays is demonstrated.